Peningkatkan Numerasi Siswa Melalui Edutainment Math Playground: Program Kampus Mengajar Angkatan 7 - Hanima, Sitti; Hasan, Hurriah Ali (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to explain the implementation of numeracy games activities through edutainment at UPT SPF SD Inpres Daya Makassar City, as well as describe the impact of improving students' numeracy skills through edutainment activities in the Batch 7 Teaching Campus program. In this study, a descriptive qualitative method is applied with an interactive analysis model approach to reveal a thorough and systematic understanding of the phenomenon studied through natural data collection. The results of the study showed that edutainment activities carried out by students of the Teaching Campus program Batch 7 proved to be effective in increasing the numeracy of students/I UPT SPF SD Inpres Daya. This is reflected in the increase in student learning motivation, active participation in learning activities and satisfactory learning outcomes. This edutainment activity is a teaching campus student team program formed through work programs carried out in placement schools, including the Edutainment Math Playground.